Measuring School–Family Conflict and Enrichment in University Student Parents: A Measurement Validation Study - van Rhijn, Tricia Marie; Acai, Anita; Lero, Donna S. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2018)
The purpose of this study was to extend work–family research to the school–family context by adapting Carlson and colleagues’ Work–Family Conflict and Enrichment scales. Using two samples of student parents primarily from Canadian universities, the adapted scales were assessed for reliability, construct validity, and factor structure. The measures had three factors for school–family conflict (school-to-family conflict, behaviour-based conflict, and family-to-school conflict) and five for school–family enrichment (school-to-family growth and affect; and family-to-school development, affect, and efficiency). The two adapted scales were confirmed to be reliable and valid for use with university student parents. Data from the confirmatory factor analysis provided strong support for the factor structure of the School–Family Enrichment Scale, but suggested that additional testing and development of the School–Family Conflict Scale may be required.